Revisiting Trump’s Protectionism and Its Policy Implications for US–Canada Trade Relations - Kaka, Yulius Mada (Politeia : Journal of Public Administration and Political Science and International Relations, 2025)
Amid the rise of economic nationalism and increasing uncertainty in global trade governance, understanding the impact of unilateral trade enforcement on bilateral relations has become critically important. This study explores the resurgence of protectionist policies under President Donald J. Trump, with a particular focus on their effects on U.S.–Canada trade relations and the broader global trend toward economic nationalism. Employing a qualitative case study approach supported by a simple tariff simulation, the research examines how instruments such as anti-dumping (AD) and countervailing duties (CVD) were utilized to protect domestic industries. The simulation indicates that imposing a 21% tariff on Canadian softwood lumber could significantly reduce import volumes while potentially increasing domestic output by 121.8%. However, these protectionist measures also intensified trade tensions, disrupted longstanding alliances, and weakened trust in multilateral institutions such as the WTO. By integrating empirical estimation with policy narrative analysis, this study contributes to the literature on trade policy, emphasizing that while unilateral protectionism may offer short-term domestic advantages, it requires careful calibration with economic diplomacy to ensure the sustainability of global trade cooperation.